Fetal Tachycardia Treated Successfully with Maternally Administered Propylthiouracil - Barbara V. Parilla; Farhan Hanif; Keren Hasbani; Thomas Iannucci (Case Reports in Obstetrics and Gynecology)
Background. Fetal tachycardia may result from the transplacental passage of thyroid stimulating immunoglobulins in a patient with hypothyroidism secondary to ablation of Graves’ disease. Case. A 32-year-old woman, gravida 4, para 2, and abortus 1, with hypothyroidism and a history of Graves’ disease, presented at 23 6/7 weeks of gestation with a persistent fetal tachycardia. The treatment of the fetal tachycardia with maternally administered digoxin and Sotalol was unsuccessful. Maternal thyroid stimulating immunoglobulins were elevated, and treatment with maternally administered propylthiouracil (PTU) resulted in a normal sinus rhythm for the remainder of the pregnancy. An induction of labor was performed at 37 weeks. Four to five days after delivery, the neonate exhibited clinical signs of hyperthyroidism necessitating treatment. Conclusion. Fetal tachycardia resulting from the transplacental passage of thyroid stimulating immunoglobulins can be successfully treated with maternally administered PTU. The neonate needs to be followed up closely as clinical signs of hyperthyroidism may occur as thyroid stimulating immunoglobulins continue to circulate in the neonate, while the serum levels of PTU decline.